2022
DOI: 10.3390/life12101469
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of CO2 Supply for the Intensive Cultivation of Chlorella sorokiniana IPPAS C-1 in the Laboratory and Pilot-Scale Flat-Panel Photobioreactors

Abstract: Microalgae are increasingly being used for capturing carbon dioxide and converting it into valuable metabolites and biologically active compounds on an industrial scale. The efficient production of microalgae biomass requires the optimization of resources, including CO2. Here, we estimated the productivity of Chlorella sorokiniana IPPAS C-1 depending on CO2 concentrations and the ventilation coefficient of the gas-air mixture (GAM) in flat-panel photobioreactors (FP-PBRs) at laboratory (5 L) and pilot (18 L) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The carbon dioxide concentration was studied for scaling up C. sorokiniana cultures in flat panel PBRs, yielding an optimal concentration at a laboratory scale (5 L) of 1.5% with a flow rate of 0.2 vvm. At a pilot scale (18 L), Gabrielyan et al (2022) found that when keeping the volumetric flow rate of CO 2 constant, the increase in the rate of aeration noticeably enhanced the growth and biomass yield. They also found that the direct transfer of specific cultivation parameters from a small to a large scale does not ensure a proportional increase in biomass yield ( Gabrielyan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The carbon dioxide concentration was studied for scaling up C. sorokiniana cultures in flat panel PBRs, yielding an optimal concentration at a laboratory scale (5 L) of 1.5% with a flow rate of 0.2 vvm. At a pilot scale (18 L), Gabrielyan et al (2022) found that when keeping the volumetric flow rate of CO 2 constant, the increase in the rate of aeration noticeably enhanced the growth and biomass yield. They also found that the direct transfer of specific cultivation parameters from a small to a large scale does not ensure a proportional increase in biomass yield ( Gabrielyan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…At a pilot scale (18 L), Gabrielyan et al (2022) found that when keeping the volumetric flow rate of CO 2 constant, the increase in the rate of aeration noticeably enhanced the growth and biomass yield. They also found that the direct transfer of specific cultivation parameters from a small to a large scale does not ensure a proportional increase in biomass yield ( Gabrielyan et al, 2022 ). To enhance the technology used to capture carbon through microalgae, improvements are required that implement environmentally friendly methods for growing microalgae, such as using flue gas and wastewater treatment technologies.…”
Section: Discussionmentioning
confidence: 97%
“…The analysis demonstrated that ROS accumulation and redox state changes are universal triggers for stress responses in cyanobacteria [184][185][186]. Unicellular coccoid green microalgae with robust growth characteristics; thermotolerant [187]; used in studies on endogenous regulation of photosynthesis and metabolism [188][189][190][191][192][193][194][195]; under stressed conditions, it accumulates mainly starch [191,192]; acts as a reference strain for biotechnological applications [175,188,189,[196][197][198].…”
Section: Use Of the Collection Strains For Fundamental Studies On The...mentioning
confidence: 99%
“…Some strains with robust growth characteristics, such as Chlorella sorokiniana IPPAS C-1 and C. vulgaris Beijerinck IPPAS C-2 have been used as reference strains for different biotechnological applications [ 175 , 196 , 197 , 198 , 199 , 200 ] ( Table 5 ), including the design and testing of the novel models of photobioreactors [ 175 , 198 ] ( Figure 14 d,e). Synechocystis sp.…”
Section: Culture Collection Of Microalgae and Cyanobacteria Ippas At ...mentioning
confidence: 99%
“…The efficiency of microalgae at assimilating CO 2 using solar energy is 10-50 times higher than that of terrestrial plants [186,187]. In terms of CO 2 , 1.0 kg of algae biomass may assimilate ~1.83 kg of CO 2 , which makes it possible to rear microalgae near thermal power plants or any other sources of greenhouse gases [181,182,188]. Currently, microalgae are actively used to obtain a wide range of biologically active components, such as proteins (including the production of amino acids), fats (including polyunsaturated fatty acids), carbohydrates (including starch and fiber), carotenoids, pigments, vitamins, and biologically active forms of major and trace elements [189][190][191].…”
Section: Technologies For Biological Co 2 Sequestration and The Produ...mentioning
confidence: 99%